Retrospective comparison of three-dimensional imaging sequences in the visualization of posterior fossa cranial nerves. Issue 97 (December 2017) - Ors, Suna; Inci, Ercan; Turkay, Rustu; Kokurcan, Atilla; Hocaoglu, Elif
Abstract: Purpose: To compare efficancy of three-dimentional SPACE (sampling perfection with application-optimized contrasts using different flip-angle evolutions) and CISS (constructive interference in steady state) sequences in the imaging of the cisternal segments of cranial nerves V–XII. Methods: Temporal MRI scans from 50 patients (F:M ratio, 27:23; mean age, 44.5 ± 15.9 years) admitted to our hospital with vertigo, tinnitus, and hearing loss were retrospectively analyzed. All patients had both CISS and SPACE sequences. Quantitative analysis of SPACE and CISS sequences was performed by measuring the ventricle-to-parenchyma contrast-to-noise ratio (CNR). Qualitative analysis of differences in visualization capability, image quality, and severity of artifacts was also conducted. A score ranging 'no artefact' to 'severe artefacts and unreadable' was used for the assessment of artifacts and from 'not visualized' to 'completely visualized' for the assesment of image quality, respectively. The distribution of variables was controlled by the Kolmogorov–Smirnov test. Samples t -test and McNemar's test were used to determine statistical significance. Results: Rates of visualization of posterior fossa cranial nerves in cases of complete visualization were as follows: nerve V (100% for both sequences), nerve VI (94% in SPACE, 86% in CISS sequences), nerves VII–VIII (100% for both sequences), IX–XI nerve complex (96%, 88%); nerve XII (58%, 46%) (p < 0.05). SPACE sequences showed fewer artifacts than CISS sequences (p < 0.002).